The peculiarities of CVD diamond coatings synthesis in abnormal glow discharge plasma using repetitively-pulsed mode; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Linnik S. A. Stepan Andreevich (Modification of materials with particle beams and plasma flows, 2017)
Title screen